PCR guru : an ultimate benchtop reference for molecular biologists - Najafov, Ayaz; Hoxhaj, Gerta (Academic Press, Elsevier, 2017)
"PCR Guru: An Ultimate Benchtop Reference for Molecular Biologists is provides researchers in molecular biology with a handy reference for approaching and solving challenging problems associated with PCR setup and optimization. As a laboratory guide, it emphasizes the technical aspects of employing PCR as a tool in molecular biology laboratories. The book covers the history of PCR and the basic science underlying it. It then discusses PCR at the bench level, starting with detailed description and tips on primer design, and continuing with the standard protocols used to perform PCR. Provides troubleshooting tips for various types of modifications of standard protocols Contains unique "Good Practices and Tips that are indispensable for the beginner and expert alike Features "Special Cases with applications of PCR, optimization, and troubleshooting Includes detailed appendices with tables, figures, and key protocols Organized as a systematic, concentrated resource to save time when addressing a PCR problem."